The Variability in Cytocompatibility and Bone Conduction Based on Different Pore Size and Porosity of n-HA/PA66 Composite Scaffolds - Liu, Yiming; Zhang, Rui; Liu, Sirui; Sun, Jingjing; Zhang, Xue; Kang, Peng; Zhang, Ruipu; Yang, Yanyu; Li, Rui (Frontiers in Materials, 2021)
To investigate the variability of n-HA/PA66 composite scaffolds on differentiation and biocompatibility, we evaluated three kinds of n-HA/PA66 composite scaffolds according to the pore size and porosity. Osteogenically induced BMSCs were seeded in the three types materials and cultured in vitro, and the variability on cell adhesion, growth, proliferation, osteogenic differentiation were analyzed using scanning electronic microscopy (SEM), immunohistochemical staining, and quantitative real-time PCR analysis. Three groups’ matrices/BMSCs composites were implanted into the cranial defect of S-D rats. The differentiations of osteogenesis were then evaluated by histological and qRT-PCR analysis The vitro and vivo results showed that the group B n-HA/PA66 scaffold was more suitable for osteogenically induced BMSCs proliferation, differentiation in vitro and bone conduction in vivo than group A and C, indicating that the porous n-HA/PA66 matrices with mean pore size of 375±132.2 μm and porosity 77 ± 2.9 % has better cell biocompatibility and bone conduction.